Reference Evapotranspiration Changes: Sensitivities to and Contributions of Meteorological Factors in the Heihe River Basin of Northwestern China (1961–2014). (29th December 2015) - Du, Chaoyang; Yu, Jingjie; Wang, Ping; Zhang, Yichi
Abstract : This paper investigates reference evapotranspiration( E T 0 ) changes, sensitivities to and contributions of meteorological factors in the Heihe River Basin (arid and inland region). Results show that annualE T 0 over the whole basin has increasing trend (2.01 mm·10 yr −2 ) and there are significant increasing spatial variations from the upper (753 mm yr −1 ) to the lower (1553 mm yr −1 ) regions. Sensitivity analysis indicates that relative humidity is the most sensitive factor for seasonal and annualE T 0 change, and the influence is negative. The sensitivity of minimum temperature is the weakest and negative. Contribution analysis shows that the main contributors toE T 0 changes are aerodynamic factors rather than radiative factors. This study could be helpful to understand the response of ecoenvironment to the meteorological factors changes in the Heihe River Basin.